ESC in the Anthropocene: Education for Sustainability and Communism - Boxley, Simon (Critical Education, 2022)
Insofar as Education for Sustainable Development still represents a redemptive intervention, one according to the demands of a monolithic improvement agenda, its chances are greatly enhanced by the restoration of Grand Narrative initiated by the epochal turning. The much vaunted Anthropocene returns to the agents of change the opportunity to redirect the unified ‘geostory’ of ‘biohistory’ towards a steadier state. That is to say, the Anthropocene collapse of the ‘human’ and ‘natural’ spheres into each other’s orbits restores to ESD its promise to heal the planetary condition. This paper proposes, though, that such a re-fertilisation of ESD can bear fruit only if its premises are radicalised, indeed revolutionised. Employing a red biocentric approach – a praxis which advocates communism without anthropocentrism – it is argued that education for sustainability under current conditions equates to teaching and learning towards collectivism, class-, species- and world-consciousness. Furthermore, it is suggested, such consciousness is meaningless without vehicles for its articulation and actualisation. This means organisation, activism, disobedience, and the emergence of the possibility of the mass Earth Strike. Education for Sustainability and Communism (ESC) is unsurprisingly an activity unconfined by classroom walls: the condition of its possibility is the real, material site of resistance and of spectacle. It is argued that in order to break the impasse between critique and transformation, ESC affords the only viable possibility for the evolution of education for development that is fit for the Anthropocene.